Physiotherapy in the physical rehabilitation of patients with sequelae of injuries of the lower extremities in Zhitomir of rehabilitation facilities - O.D. Zhelezniy; G.B. Zasik; V.M. Mukhin; N.O. Skliarova (Pedagogics, Psychology, Medical-Biological Problems of Physical Training and Sports, 2015)
Purpose : to study the physical properties and therapeutic effect of mechanical factors in the pathogenetic treatment in traumatology. Material : 622 patients were studied with the consequences of injuries of the lower extremities (age 18-64 years). Observations carried out since 2005 in hospitals and medical health institutions of Zhitomir. Selected physiotherapy factors that are mainly used for the physical rehabilitation of patients in trauma. Results : identified the factors that were intended to eliminate the consequences of injuries of the lower extremities. Analyzed their effect in the author's method of complex rehabilitation of patients. Performed systematization selected physiotherapy factors in a table to read and understand forms. In the medical health institutions in the city of Zhytomyr investigated and established the effectiveness of the recommendations. Conclusions : physical factors cause the body general, non-specific and specific response to each type of impact. This allows you to selectively influence the pathogenic elements of the disease. Should strictly adhere to the indications and contraindications to the use of physiotherapy factor. It is necessary to take into account age, sex, and comorbidity.